2017
DOI: 10.3892/ol.2017.5684
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA-615-3p as a novel tumor suppressor in non-small cell lung cancer

Abstract: Abstract. Lung cancer is the most frequent cause of mortality in cancer patients; non-small-cell lung cancer (NSCLC) accounts for ~80% of lung cancer cases. MicroRNAs (miRNAs) have been revealed to perform an important role in cancer development and progression. Based on a custom miRNA microarray analysis of patients with NSCLC, miRNA-615-3p (miR-615-3p) downregulation was identified in NSCLC tissues compared with normal lung tissues, which suggested that miR-615-3p acted as a tumor suppressor in lung cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…In addition, bioinformatic analysis predicted that HSF1 was a target gene of microRNA-615-5p, which was confirmed by a dual luciferase reporter assay. The present study is consistent with previous studies, which demonstrated that microRNA-615-5p functions as a tumor suppressor (12), whereas HSF1 serves as a tumor promoter (13).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, bioinformatic analysis predicted that HSF1 was a target gene of microRNA-615-5p, which was confirmed by a dual luciferase reporter assay. The present study is consistent with previous studies, which demonstrated that microRNA-615-5p functions as a tumor suppressor (12), whereas HSF1 serves as a tumor promoter (13).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, in nonesmall-cell lung cancer, miR-615-3p expression has been identified as down-regulated in tumor samples compared with normal tissue samples and to inhibit cell proliferation and migration in vitro. 34 The seeming discrepancy in regard to the role of miR-615-3p as either an oncomiRNA or a tumor suppressor in different malignancies indicates that miR-615-3p functions in a highly cell-and disease-typeespecific manner. This may be explained, at least in part, by differences in target genes, as has previously been demonstrated for many other miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…While, miR-615-3p plays important role in the differentiation of cells, it suppresses GDF5 and FOXO1 and inhibits osteogenesis in the lumbar ligamentum flavum cells [ 269 ], it is also known to have a feed-forward loop with HOXC5, and repress hTERT during the differentiation of cells [ 270 ]. In cancer, miR-615-3p plays a dual role depending on the type, for example, it promotes gastric cancer potentially by targeting CELF2 [ 176 ] and prostate cancer [ 177 ], but reported to be a suppressor of NSCLC potentially targeting IGF2 [ 178 , 179 ] and esophageal cancer [ 180 ]. In addition, it could be used as a biomarker for the recurrent HCC [ 181 ] and also regulates lipoapoptosis by targeting the C/EBP homolog in mice [ 271 ].…”
Section: Micrornas In the Regulation Of Ribosomal Protein Coding Mmentioning
confidence: 99%